Population Genomics Provides Insights Into Genomic Features of Inbreeding Depression in Arma Chinensis - Bin Li; Kangkang Song; Zixian Wu; Xiaohua Zhang; Haozhen Li; Long Yang (Evolutionary Applications)
ABSTRACT Arma chinensis, a predatory insect renowned for its prey diversity in East Asia, is effective in controlling agricultural and forestry pests. However, after introducing field populations into indoor subcultures, features of inbreeding depression have surfaced within these populations. Clarifying the molecular genetic mechanism of inbreeding depression of A. chinensis is of great significance for its population protection. In this study, phylogenomic analysis revealed that the genus Arma shared a common ancestor with Halyomorpha and Nezara in the Pentatomidae family around 63.62 million years ago. Based on whole‐genome resequencing of three consecutive inbred generations of A. chinensis, we investigated the genomic features of inbreeding depression. We observed an accumulation of long runs of homozygosity and extreme variations in nucleotide diversity across generations, collectively affecting 111 genes and multiple biological processes, such as sequence‐specific DNA binding, synapse organization, and transcription regulatory region binding. These genomic changes suggest that successive inbreeding may disrupt normal physiological functions, potentially impairing gene expression, neural signaling, and sensory organ development. In conclusion, our study clarifies the evolutionary position of A. chinensis, highlights the genetic consequences of inbreeding, and emphasizes the importance of preserving genetic diversity in natural populations for long‐term survival and adaptability.